PROBLEMS OF SOCIAL HEALTH IN MODERN SOCIETY - Bortnyuk, Olga Anatolievna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Relevance   of the topic  is determined by the social need for the care about social health as integral part modern public lives. Locate in article prerequisites strengthening and preservations of social health of the modern person. Purpose.  Consider approaches to research of a phenomenon of health in system social and humanitarian knowledge. Results.  The article synthesis of theoretical provisions and proposes reorganization of forms and methods of social work on health protection and to prevention of risk of diseases the younger generation. Practical implications.  The results of the study can be used to the problems of social health of today’s youth, as well as in the educational process as a whole.